Response of Calliandra calothyrsus to inoculation of mutant strain of rhizobia - N.D Purwantari; E Sutedi (Jurnal Ilmu Ternak dan Veteriner, 2005)
Rifampicin mutants of rhizobial strain CB3171rif50 and CB3090rif100 were the most effective nitrogen fixing strain of rhizobia selected under axenic condition. An experiment was conducted to evaluate the symbiotic response of C. Calothyrsus inoculated by CB3171rif50 or CB3090rif100 grown in the field, on latosol soil with pH 5,2. Plants were either (1) inoculated with mutant strain CB3171rif50, (2) inoculated with mutant strain mutant CB3090rif100 (3) uninoculated and without nitrogen addition or (4) uninoculated and with nitrogen fertilizer as a basal fertilizer. Treatments were replicated four times and arranged in Randomized Complete Block Design. Parameters measured were plant height at early stage of the growth, leaf weight, stem weight, nodule number and weight, proportion of nodule formed by inoculant, N and P content of leaf. Results shows that C. calothyrsus was responded to Rhizobium inoculation. The rate of regrowth was faster for the inoculated plant than that of uninoculated and no nitrogen addition. CB3171rif50 produced significantly (P<0.05) the highest leaf fresh and dry weight. At the first harvest (10 month-old of plant) it produced 2106 g/tree that equivalent to 18.72 ton/ha. The lowest was achieved by uninoculated plant which was 556 g/tree that equivalent to 4.94 ton/ha. The production of shoot was increased at the subsequent harvests. CB3171rif50 was out yielded in all harvest, except for the second harvest. The highest total production of leaf fresh weight was obtained by plant inoculated with strain mutan CB3171rif50 which was 50.62 ton ha-1 year-1, followed by CB3090rif100, which was 39.75 ton ha-1 year-1 and the lowest was obtained by uninoculated plant, in a range of 29.64–30.62 ton ha-1 year-1. Nodule recovery shows that nodule samples from uninoculated plant were not resistant to 50 ppm and 100 ppm rifampicin antibiotic that means not producing mutant strain, indicating that those nodules were from the native rhizobial strains. Recovery of nodules showed that proportion of nodules infected by strain mutant CB3171rif50 was 61.3% from nodules tested and nodules infected by CB3090rif100 was 20%. Both mutant strains inoculation have increased the plant production and reinoculation was not necessary till 19 month-old of the plant. Re-inoculation should be considered after this period.     Key Words: Calliandra calothyrsus, Rhizobium, Mutant, Inoculation